Dežela - knez - stanovi Oblikovanje kranjskih deželnih stanov in zborov do leta 1518 - Nared, Andrej (Thesaurus memoriae, 2009)
The scientific monograph Dežela - knez - stanovi [Province - Duke - Estates] describes the formation of Carniolan provincial estates at the time when they completed their constitutional consolidation and obtained a constructive political equilibrium with the duke. The central part reconstructs the composition of the Carniolan estates within the first century of their existence and the operations of the provincial diet until the death of Emperor Maximilian I. The monograph covers almost two centuries of the late medieval and early modern political and constitutional history. In doing so, it does not limit itself to the Province of Carniola, but discusses it in relation to other Habsburg provinces. This is the first complex presentation of the problem, based on a wide array of sources and comparisons with the development in the neighbouring countries. The work represents a research into an important question concerning the Carniolan as well as broader Slovenian history at the turn of the Middle Ages and Modern Period. It is a broadly based study and the first of its kind in Slovenian historiography to address the selected theme. Moreover, the monograph also bears importance for the broader, especially Austrian-German area.The book is divided into eleven chapters. It also contains an extensive summary in German, as well as an index of names and a subject index. The text is accompanied by three maps and thirty-four illustrations.